К вопросу о “простом” языке в Московской Руси (псалтырь Аврамия Фирсова) - Целунова, Е.А. (Kalbotyra, 1985)
At the end of the 17th c. in Moscow Russia there appeared books written in the “prostoi jazyk” (literally “simple” language). The earliest of the books of this kind is the Psalter by Avramy Firsow (1683). Three manuscripts of this Psalter are known nowadays. The study of the language and style of these manuscripts will extend our knowledge of the “simple” language in Moscow Russia.